Neonatal Pemphigus in a Neonate of a Mother Suffering from Pemphigus Vulgaris- A Case Presentation - Sandeep Kulkarni; Pooja Jaideep Sahu; Aishwarya Patil; Bhushan Madke; Vikrant Saoji (Journal of Clinical and Diagnostic Research, 2020)
Neonatal pemphigus is a transient, self-limiting entity featuring appearance of evanescent blisters in a neonate born to mother diagnosed with immuno-bullous blistering disorders. A case report of neonatal pemphigus born to a 30-year-old female with Pemphigus Vulgaris is being reported. Higher maternal antibody titre causing clinically evident blistering in neonate is not commonly reported. This report, thus, emphasises the need for diagnostic considerations and vigilant surveillance of neonatal pemphigus in neonates born to mothers with immunobullous disorders. Since the cases reported in the literature and the references assessed revealed that neonatal pemphigus is infrequent, but the understanding about the disease permits for an early diagnosis to be made.